Holocene environmental variability inferred from lake sediments, southwest Yukon Territory, Canada - Bunbury, Joan (University of Ottawa (Canada), 2009)
Lake sediment cores collected from four lakes (Upper Fly Lake 61.04°N, 138.09°W, 1326 m a.s.l.; Jenny Lake 61.04°N, 138.36°W, 817 m. a.s.l.; Donjek Kettle 61.69°N, 139.76°W, 732 m a.s.l.; Lake WP02 61.48°N, 139.97°W, 1463 m a.s.l.) in the southwest Yukon provide records of postglacial climatic variability in the region. A 13,000 year pollen record from Upper Fly Lake indicated that herbaceous tundra existed on the landscape from 13.6 to 11 ka, followed by birch shrub tundra until 10 ka, when Picea forests were established in the region. Pollen-, chironomid-, and ostracode-inferred paleoclimate reconstructions showed a long-term cooling with increasing moisture from the late glacial through the Holocene. The early and mid-Holocene were warm and dry, with cool, wet conditions after 4 ka, and warm, dry conditions over the last 100 years. Chironomid accumulation rates provided evidence of millennial-scale climate variability, and the chironomid community responded to rapid climate changes. Late Holocene environmental variability was investigated through the analysis of paleoproduction indices (sediment loss-on-ignition, biogenic silica) and chironomid and ostracode communities. Coherent trends were revealed among the four lakes and pairs of sites located closer together showed more similarities than more distant sites located in similar environments (alpine tundra or boreal forest). Chironomid-inferred paleotemperature estimates are inconsistent with other data from the region, however certain fluctuations in paleoproduction indices and changes in abundance and composition of the chironomid and ostracode communities compare well with interpretations based on independent paleoclimate records. The White River Ash event (1147 cal yrs BP and 1953 cal yrs BP) impacted three of the four aquatic ecosystems studied, with a greater impact occurring at sites with greater ash thickness. Interannual variability in the lake environment is of lesser concern when deriving inference models relating organisms to environmental variables, and the results presented here provide guarded optimism that the sampling methodology applied in paleolimnological studies is appropriate in this region.
Keywords: Geography.; Climate Change.; Sedimentary Geology.; Paleoclimate Science.